Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1177/0020764017723669
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a patient-illness representations of depression of Anglo-Australian and Sri Lankan patients through the lens of Leventhal’s illness representational model

Abstract: Findings highlight the importance of forging a shared understanding of patient beliefs in the clinical encounter to ensure that interventions are coherent with illness beliefs or at least work towards improving mental health literacy. Differences in illness beliefs also provide insights into possible interventions. For example, psychosocial interventions that align with their illness beliefs may be more suited to Sri Lankan migrants than pharmaceutical or psychological ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
(76 reference statements)
3
7
0
Order By: Relevance
“…In Sri Lanka, patients would resort to spiritual healing methods before consulting a psychiatrist (Chandradasa & Kuruppuarachchi, 2017). A similar trend of reluctance to engage in pharmacotherapy was seen among the Sri Lankans in Australia (Antoniades et al, 2017).…”
supporting
confidence: 53%
See 2 more Smart Citations
“…In Sri Lanka, patients would resort to spiritual healing methods before consulting a psychiatrist (Chandradasa & Kuruppuarachchi, 2017). A similar trend of reluctance to engage in pharmacotherapy was seen among the Sri Lankans in Australia (Antoniades et al, 2017).…”
supporting
confidence: 53%
“…In contrast, another patient may attribute the causality of the illness to Karmic fate and feel helpless, suggesting an external locus of control (Phillips et al, 2012). As found in the study, Sri Lankans attribute difficulties arisen due to depression on to situational triggers (Antoniades et al, 2017), as perceived to be caused by past Karma. They would be hopeful that once the Karma is spent, their situation and health would improve.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Studies that have examined IRs among individuals with depression have shown that they perceived the disorder as chronic, and as having many symptoms and negative consequences for their lives, but as being controllable nevertheless (Abo-Rass et al, 2020a; Antoniades et al, 2017; Baines & Wittkowski, 2013; Brown et al, 2007; Ward et al, 2014). In addition, in earlier studies, depression cognitive IRs were found to be significantly related to various health outcomes such as coping strategies, help seeking, and treatment adherence (Alderson et al, 2012; Baines & Wittkowski, 2013; Care & Kuiper, 2013; Glattacker et al, 2012; Hagerty et al, 2018; Ward et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The utility of the CSM for understanding the psychosocial implications of physical illness has been demonstrated in different types of conditions (Hagger & Orbell, 2003) such as asthma (Achstetter, Schultz, Faller, & Schuler, 2019), cancer (Postolica, Iorga, Savin, Azoicai, & Enea, 2018), and brain injuries (Snell, Hay-Smith, Surgenor, & Siegert, 2013). In addition, there has been a growing interest in using the CSM in the context of mental illness (Antoniades, Mazza, & Brijnath, 2017;Scerri, Saliba, Saliba, Scerri, & Camilleri, 2019).…”
Section: Introductionmentioning
confidence: 99%